2021
DOI: 10.1177/00469580211060788
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Magnitude of Nurses With the Use of Health Information Exchanges: Analyzing the National Health Insurance Claim Data of Hospitals and Clinics in Korea

Abstract: Background Many features of health care organizations (HCOs) have been identified to be associated with health information exchange (HIE), but subcategories of organizational factors focusing on nurse workforces still need to be identified. The objective of this study is to investigate the association of number of nurses with HIE use in Korea. Methods This study had a retrospective study design and used health insurance claim data from June 1, 2016 to June 30, 2018. The unit of analysis was the HCO, and any he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Nevertheless, there was a statistically significant correlation between the number of m-PHR applications in hospitals and the quality of care regarding antibiotic drug use. The results of this study were similar to those of previous studies, which found that hospitals with active health information exchanges typically had good nursing manpower infrastructure, and hospitals providing high-quality care were more likely to adopt the m-PHR system [ 7 , 20 ]. This suggests that hospitals with excellent infrastructure and high-quality care might be interested in improving customer services, such as adopting and using the m-PHR system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, there was a statistically significant correlation between the number of m-PHR applications in hospitals and the quality of care regarding antibiotic drug use. The results of this study were similar to those of previous studies, which found that hospitals with active health information exchanges typically had good nursing manpower infrastructure, and hospitals providing high-quality care were more likely to adopt the m-PHR system [ 7 , 20 ]. This suggests that hospitals with excellent infrastructure and high-quality care might be interested in improving customer services, such as adopting and using the m-PHR system.…”
Section: Discussionsupporting
confidence: 86%
“…M-PHR systems are also known to be effective in chronic disease management [ 16 , 17 , 18 , 19 ]. Healthcare institutions with more health information exchanges tend to have a well-composed medical staff [ 20 ]. In these respects, hospitals that provide high-quality care may have a higher number of m-PHR downloads than others.…”
Section: Introductionmentioning
confidence: 99%
“…They found that satisfaction and attitude were Findings from the 2022 Yearbook Section on Health Information Exchange the only dimensions that predicted continued use. Park et al, looked at structural factors in hospitals that had varying rates of HIE usage in Korea [17]. They found that the extent of HIE use was related to the number of nurses and the nurse-to-bed ratio.…”
Section: Facilitators and Barriers To Hiementioning
confidence: 99%